Synthesis of shape memory polymers for sports apparel - Tan, Rachel Li Zhen (2018)
Shape memory polymer have been extensively studied due to the ability to recover to its original shape upon exposing to an external stimulus. This report demonstrates poly(ethylene glycol) are shape memory polymer that has been synthesized and characterized. Poly(ethylene glycol) network are cross-linked by free radical polymerization of hydroxyl groups at the end of PEG chain that were methacrylated and converted into demonstrated poly(ethylene glycol) diamethacrylation. Poly(ethylene glycol) are being cross-linked with two different additives, namely, butyl acrylate and styrene which are examining the one-way and two-way shape memory effect. The degree of cross-linking of the networks was determined by the gel fraction which is higher than 80%. The methacrylation process, thermomechanical properties and shape memory effect of the shape memory polymer networks were characterized by Fourier-transform infrared spectroscopy, differential scanning calorimetry, mechanical tensile test and dynamic mechanical analysis. Fourier-transform infrared spectroscopy showed the success of f hydroxyl groups at the end of poly(ethylene glycol) chain were methacrylated and then cross-linked with additives. Different percentage of additives were employed with the goal of achieving a better mechanical properties and shape memory effect. 40wt% styrene and butyl acrylate showed good soften effect while 20% Styrene showed a good thermal responsive two-way reversible shape memory effect between 37℃ and -20℃ with a recovery percentage of 56.11% respectively. The shape memory properties of the networks showed a shape fixity higher than 79% and a minimum recovery ratio of 80%.